Метод определения долевого участия субъектов в нарушении симметрии по мощности симметричных составляющих при длительных измерениях потребления электрической энергии - Сендерович, Геннадий Аркадиевич; Дяченко, Александр Васильевич (НТУ "ХПИ", 2017)
Предложен метод определения долевого участия потребителя в ответственности за нарушения симметрии напряжения в точке общего присоединения с использованием локального измерительного устройства. Метод основан на расчете электроэнергии, по которой требуется определение ответственности потребителя. В дальнейшем могут быть разработаны методика и алгоритм реализации нового метода в соответствии с нормами оценки показателей качества электрической энергии и удобства использования в условиях эксплуатации.

The method of determination of individual share of a customer in responsibility for violation of symmetry of tension in a point of the general association with use of the local measuring device is offered. This method allows to approach an assessment of an error which is caused by the mutual component of power arising in the presence of two and more sources of distortion of symmetry in a different way. The main feature of a method is the possibility of its use by the analysis of the parameters of the mode measured only on buses of a customer. Further the technique and an algorithm of implementation of this new method according to norms of an assessment of figures of merit of electrical energy and usability under operating conditions can be developed. What in turn will allow to include it in a complex technique of determination of individual share of subjects in responsibility for violation of quality of the electric power.
Method of definition of individual share of subjects in violation of symmetry on the power of symmetric components at long measurements of consumption of electric energy
Keywords: качество электроэнергии; симметрия напряжения; активная мощность обратной последовательности; сопротивления связи; интервал усреднения; локальное измерительное устройство; quality of the electric power; symmetry of tension; active power of the return sequence; communication resistance; averaging interval; local measuring device